Developing A Local Culture Based Video Learning Prototype For English Speaking Skill (A Study for 7th Graders at SMPN 15 Bengkulu City Academic Year 2024-2025) - Sella, Winda Firama (Jurnal Kajian Ilmu Pendidikan (JKIP), 2025)
The purpose of this study was to develop a product for developing English speaking learning media based on video on Bengkulu local culture material for 7th grade junior high school students in the 2023/2024 academic year. The product is based on video learning media, which is the development of learning media in the form of videos. This study aims to identify local culture into the form of video learning media which is expected to improve the quality of student learning. After being validated by an expert validator, the product was revised and tested on 7D grade students of SMP Negeri 15 Kota Bengkuu to determine student responses to the developed learning media. The results of the validation test were 91.6%, these results fall into the assessment criteria of 81.00% - 100.00% with the categories very valid, very effective, very complete, can be used without improvement. The results of the trial were 77.41%. The results of the trial showed that the product developed in this study was effective in improving students’ English speaking skills.